Are we Clean Enough? A Cross Sectional Study Conducted among General Dental Practitioners and Consultants of Karachi - Kashif, Mehwash; Kamran, Muhammad Abdullah; Ayub, Tahera; Hussain, Syed Sheeraz; Khan, Muhammad Irfan (Journal of Liaquat University of Medical & Health Sciences, 2020)
Objective: To assess the connection between dentist qualification and adequacy of sterilization and to determine practices of dentist against Infection control. Methodology: This cross-sectional study was conducted from January to June 2018. General dental practitioners and consultants with minimum clinical practice period of one or more than one year were included in the study. The exclusion criterion included general dental practitioners and consultants who did not give consent for study. A questionnaire including basic demographic data, personal protection and cross infection control measures, instrument sterilization and operatory disinfection from the General Dental Practitioner Surgeons and consultants. Total 89 clinicians were asked for their practice of sterilization and disinfection. Data was entered and analyzed on SPSS version 13. Results: According to the results mean age was 31.80±9.27 years. Results showed that the GDPs were 57.8% and consultants were 42.2%. Males were 46.7% and females were 53.93 %. Mean working experience was 7.80 years and number of practicing hours per day were 6.20. Association between dentist’s qualification (general dental practitioners and consultants) and different methods of sterilization were evaluated which shows significant p-value i.e. <0.05. The variables with significant p-value were disinfecting operatory at the end of the day i.e. 0.013 and biological sporing test i.e. 0.0175. The practices of dentist against Infection control were also assessed. Conclusion: It was concluded that the connection between dentist qualification and adequacy of sterilization in some aspects was significant, those having higher qualifications than simple graduates were doing daily and prompt sterilization.